La enseñanza aprendizaje de la investigación. Representación social desde la perspectiva estudiantil - Loli Ponce, Rudi Amalia (2015)
The university is the space where creativity and the true spirit of research on students and teachers who are engaged in the process of learning of the research process on which there are different paradigms, stereotypes, prejudices and perceptions is developed, which occur in the socio-cultural context. Objective: To describe the social representation of nursing students from a medical school on the learning of undergraduate research. Design: interpretive qualitative descriptive study based on the theory of social representations. Institution: Faculty of Medicine, National University of San Marcos. Lima, Peru. Participants: undergraduate nursing students. Methods: We used techniques and instruments for data collection focus groups and free and systematic observation. Main outcome measures: social representation on the learning of the investigation. Results: The social representation of students emerged three categories: (1) facing new learning, (2) building the research project, and (3) understanding the significance of research. Conclusions: The social representation of the learning of the investigation of nursing students was presented as difficult, complex, stressful, which is related to the pressure and teachers disputes, work overload and that implies values ​​such as perseverance, dedication and time. Moments considered more difficult and important are the problem statement, the operationalization of variables and lift. Favorable attitudes research shows; however, there is a dichotomy: "I like it, but ... well, I do not have time."